(untitled) (Geologica Macedonica, 2014)
The latest explorations and study of the Kazan Dol locality displayed interesting lithogeochemistry and soil geochemistry results. Very indicative were copper contents of up to 9942 ppm Cu, zinc up to 1235 ppm Zn, lead up to 5501 ppm Pb, molybdenum up to 24 ppm Mo, etc. These anomalous zones were direct product of copper vein mineralizations in oxidation zones, which have been confirmed with later exploration drill holes. In some individual samples, from trenches and drill holes, copper content reached up to 4% Cu while the more common content is around 0.4% Cu. More than 27 drill holes were chosen for the construction of the 3D model of the Kazan Dol mineralized area, Republic of Macedonia. With use of the professional software ArcGIS was prepared 3D model of the deposit, which reflects the mineralization between level 340 and 180. This particular model should improve our understanding of the copper bearing mineralizations in this area. Key words: 3D model; Kazan Dol deposit; copper vein type; soil geochemistry